Pengembangan Model Pembelajaran: Discovery Learning dan Model Group Investigation pada Mata Pelajaran Bahasa Indonesia Kelas VII SMP - Ester Telaumbanua; Agus Mesrawati Gea; Waozatulo Giawa; Trisman Harefa (Journal on Education, 2023)
Discovery Learning and Group Investigation (GI) learning models were both used by researchers in this study. Formulation, in particular: How does Discovery Learning work best? 2) At what stage is the discovery learning model developed? The researcher uses a qualitative descriptive data analysis method, which means developing ideas or conducting data analysis based on the results as they are. So that they can assist in the teaching and learning process, this research examines how to build a mixture of learning models that will be used in the future. From the research results it is known that both of the models can be combined into one model because each phase or learning syntax can complement each other.